Proceedings of the 2003 Bipolar/BiCMOS Circuits and Technology Meeting (IEEE Cat. No.03CH37440)
DOI: 10.1109/pac.2003.1288643
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning of RHIC deuteron-gold collisions

Abstract: Deuteron and gold beams have been accelerated to a collision energy of 6 = 200 GeVfa in the Rehtivistic Heavy Ion Collider (RHIC), providing the fkst asymmetric-species collisions of this complex. Necessaxy changes for this mode of operation include new ramping software and asymmetric crossing angle geometries. This paper reviews machine pedormance, problem encountered and their solutions, and accomplishments during the 16 weeks oframp-up and operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…However the heavy-ion physics programme at the LHC is expected to include further stages not yet scheduled within the CERN programme. These may include: p-Pb collisions are a crucial element of the physics programme, just as d-Au collisions are at RHIC [15]. A preliminary study [16] has shown that the injector chains for protons and ions can work in tandem to efficiently fill the two LHC rings with matching bunch trains.…”
Section: Beyond Pb-pb Collisionsmentioning
confidence: 99%
“…However the heavy-ion physics programme at the LHC is expected to include further stages not yet scheduled within the CERN programme. These may include: p-Pb collisions are a crucial element of the physics programme, just as d-Au collisions are at RHIC [15]. A preliminary study [16] has shown that the injector chains for protons and ions can work in tandem to efficiently fill the two LHC rings with matching bunch trains.…”
Section: Beyond Pb-pb Collisionsmentioning
confidence: 99%
“…In the first asymmetric run in 2003, d and Au beams were initially injected and accelerated with the same rigidity, resulting in different revolution frequencies [61]. This lead to modulated long-range beam-beam interactions, including tune modulations [62], which resulted in unacceptable beam loss and emittance growth.…”
Section: Acceleration Of Asymmetric Speciesmentioning
confidence: 99%
“…The setup and performance of the collider during Runs 7 and 3 are summarized in [3] and [4] respectively. The deuteron beam intensity in RHIC was 1.2 x 10 11 per bunch.…”
Section: Preparation For Deuteron-gold Operations In Run-8mentioning
confidence: 99%